NATMAP – Canada’s National Geoscience Mapping Program: 1991 – 2003 - Robertson, Blyth (Geoscience Canada, 2010)
SUMMARY The National Geoscience Mapping Program (NATMAP) was developed by the Geological Survey of Canada (GSC) in 1991 to support Canada’s natural resources industry by filling gaps in the fundamental geoscience database, and to respond to emerging environmental and societal issues. The 12-year, multi-million dollar program operated through close collaboration between the GSC and the provincial and territorial geoscience agencies; it also incorporated participation from universities and some support from industry. Projects ranged from mapping and assessing the surficial geology of the Oak Ridges Moraine in Greater Toronto, documenting the geological framework of the Slave Province in the Northwest Territories, to research on the evolution of oil and gas in the Magdalen Basin off Canada’s east coast. The program, whose thirteen projects included components in nine provinces and three territories, came to a successful end in 2003. Now, almost twenty years after fieldwork began on the first of the NATMAP projects, impacts of this major contribution to Canada’s geoscience realm have been recognized from several perspectives. As expected, a wealth of new, high-quality geoscience knowledge was acquired for various areas across Canada, knowledge that became and remained readily accessible. Early socio-economic impacts from applying this knowledge can now be recognized and documented. In addition, NATMAP’s legacy must also include recognition of how it led to establishing an important and effective framework under which cooperative and collaborative geoscience is designed and conducted by GSC and provincial and territorial geoscience agencies, and also how the organization of NATMAP became the first step in the evolution of the way in which the GSC plans and undertakes the whole of its geo-science program in response to meeting the varied geoscience needs of Canadians. Perhaps a final testament to the success of NATMAP resides with many of this country’s young geologists, now following professional careers in the public and private sectors, who received invaluable training as student participants in one or another of the NATMAP projects.